Strategy of Nematophagous Fungi in Determining the Activity of Plant Parasitic Nematodes and Their Prospective Role in Sustainable Agriculture - Al-Ani, Laith Khalil Tawfeeq; Soares, Filippe Elias de Freitas; Sharma, Ashutosh; de los Santos-Villalobos, Sergio; Valdivia-Padilla, Ana Victoria; Aguilar-Marcelino, Liliana (Frontiers in Fungal Biology, 2022)
In this review, we supply a framework about the ‎important of NF and their role in agricultural ecosystems. We characterize the taxonomy, diversity, ecology, and type of NF, depending on their interaction with plant parasitic nematodes. We described potential mechanisms of NF in the control of plant parasitic nematodes, efficiency ‎and methods of utilisation, and use of nematicides‎ in sustainable agriculture. We explain the use of NF in nanotechnology as a new approach. NF are significant in the soil for having the effective ‎potential for use in sustainable agriculture. These fungi belong to wide taxa groups, such as Ascomycota Basidiomycota, and among other groups. Diverse NF are available in different kinds of soil, especially in soils that contain high densities of nematodes. There is a relationship between the environment of nematodes and NF. NF can be divided into two types according to the type of mechanisms that affect nematodes. These types are divided into direct or indirect effects. The direct effects include the fife group, ectoparasites, endoparasites‎, cyst or egg parasites, those producing toxins, and those with attack tools as special devices. However, the indirect effect comprised two groups: paralysing toxins and the effect on the life cycle of nematodes. We explained the molecular mechanisms for determining the suitable conditions in brief and clarified the potential for increasing the efficacy of NF to highly impact sustainable agriculture in two ways: directly and indirectly.